Fasting plasma glucose, diagnosis of gestational diabetes and the risk of large for gestational age: a regression discontinuity analysis of routine data. (26th September 2021) - Tennant, PWG; Doxford‐Hook, E; Flynn, L; Kershaw, K; Goddard, J; Stacey, T
Abstract : Objective: To estimate the causal effects of fasting plasma glucose (FPG) and diagnosis of gestational diabetes (GDM) on birthweight and the risks of large for gestational age (LGA). Design: Regression discontinuity analysis of routine data. Setting: Two district general hospitals in West Yorkshire, UK. Population: A cohort of 7062 women with singleton pregnancies who were screened for GDM and gave birth to a baby at ≥24 weeks of gestation in 2017–2019, inclusive. Methods: The causal effects of FPG and GDM diagnosis were estimated using the two‐stage least‐squares approach, around the diagnostic threshold of FPG ≥ 5.6 mmol/l recommended by the UK's National Institute for Health and Care Excellent (NICE), controlling for ethnicity, maternal age, parity, height and weight. Main outcome measures: Birthweight (standardised for sex and gestational age) and large for gestational age (standardised as birthweight above the 90th centile). Results: For each 1 mmol/l increase in FPG the observed birthweight increased by Z‐score = 0.48 standard deviations (95% CI 0.39 to 0.57) and the odds of LGA increased by OR = 2.61 (95% CI 1.86 to 3.66). Conversely, GDM diagnosis reduced the observed birthweight by Z = −0.61 (95% CI −0.94 to −0.29) and lowered the odds of LGA by OR = 0.33 (95% CI 0.15 to 0.74). Similar, but less certain, patterns were observed for caesarean section, shoulder dystocia and perinatal death. Conclusions: The relationship between FPG and LGA is potent but is dramatically reduced by GDM diagnosis (and all the consequences thereof). Women with mild hyperglycaemia (with an FPG of 5.1–5.5 mmol/l) who fall below the current NICE threshold for GDM diagnosis have the highest risks of adverse outcomes, suggesting a need to reconsider their current care. Tweetable abstract: Regression discontinuity analysis shows that untreated mild hyperglycaemia increases the odds of large for gestational age, but that a diagnosis of gestational #diabetes lowers the odds by three times. Tweetable abstract: Regression discontinuity analysis shows that untreated mild hyperglycaemia increases the odds of large for gestational age, but that a diagnosis of gestational #diabetes lowers the odds by three times. Linked article This article is commented on by S John and KS Joseph, p. 90 in this issue. To view this mini commentary visit https://doi.org/10.1111/1471-0528.16939 .